STRATEGI PENINGKATAN MUTU DAN CITRA (IMAGE)SEKOLAH DASAR NEGERI DI UNGARAN, SEMARANG - Maamarah, Siti; Supramono, Supramono (Universitas Kristen Satya Wacana, 2016)
This study aimed to determine the root of the problem of low quality and image of SDN 02 and 04 Ungaran and also to define the strategie to improve the quality and to build the image of SDN 02 and 04 Ungaran. This qualitative descriptive study used fishbone analysis and data collection used Focus Group Discussion (FGD), interviews, and study of document. The results showed that the root problem of low quality of SDN 02 and 04 Ungaran were learnershad low ability, teachers provided less motivation of learning, the willingness of teachers to improve teaching skills were low, teachers were elderly, teachers did not plan learning activities by themselves, school principle had never participated in managerial training, non standard size of classrooms and the library had not been adequate. The root of the problem why the image of SDN Ungaran 02 and 04 were not good enough namely: the lack of academic supervition and extracurricular competent. Strategies to improve the quality and to build image of SDN 02 and 04 Ungaran were : a)implementing ongoing supervision by principle to raise teachers motivation, b)proposing for aid to the authorities both for the rehabilitation of classrooms and procurement of books, c) involving school committee in order to improve the school environment, and d) forming school developer team in academic achievement and extracurricular activities.